THE USE OF TECHNOLOGY IN ENGLISH CLASSESS AT SMA NEGERI 1 GIANYAR: STUDENTS’ AND TEACHER’ PERCEPTION - Ida Ayu Putu Anugrah Widiantari; Luh Putu Artini; Ni Luh Putu Eka Sulistia Dewi (Esteem Journal of English Education Study Programme, 2024)
The purpose of the study was to find out how instructors and students felt about using technology in English classes. A mixed method sequential exploratory design was used in the investigation. The subjects were 228 students in the tenth grade at SMA Negeri 1 Gianyar and one English teacher. The interview guide and questionnaire were used to gather respondents' perceptions in order to meet the research goal. A combination of quantitative and qualitative analysis was used to analyze the data. The results showed that: (1) English teachers saw the use of technology in language instruction favorably because it had a number of positive effects; and (2) students believed that using technology in the language learning process could improve their knowledge and proficiency in the language. It showed that incorporating technology into the English language learning process has several positive effects on EFL students as well as English teachers.